Tomodensitometry and radioisotopic methods in the study of unilateral lung hyperlucencies of vascular origin. - Baganha, M F; Marques, M A; Botelho, M F; Teixeira, M L; Carvalheira, V; Calisto, J; Silva, A; Fernandes, A; Torres, M; Brito, J (Acta Médica Portuguesa, 1993)
Among the causes of the radiological entity known as unilateral or total hyperlucent lung is the decreased blood flow in the lungs. Unilateral and total hyperlucent lung results, among other factors, from the decreased intrapulmonary blood flow. Classically, the diagnosis and haemodynamic evaluation of these situations were usually made through invasive methods: right heart catheterism to perform angiopneumography and pressure evaluations as well as oximetry at several levels of the vascular network, thoracic aortography eventually associated with selective arteriography to detect the abnormalities of the systemic thoracic circulation. In this context, the authors propose for the diagnosis and study of this pathology, a new non-invasive methodology. In order to achieve this propose, we studied 8 patients, all of them performed clinical and laboratory evaluations, chest chi-ray, electrocardiographic and functional respiratory exams, as well angiopneumography, thoracic aortography tomodensitometry including qualitative (to study the lung arterial vasculature) and quantitative (to evaluate CT density of each lung in Hounsefield unit and two radioisotopic tests, including a ventilation/perfusion study with 133 chi e and HAM-99mTc, through an original software–four parameter histograms allowing simultaneous information of ventilation and perfusion at the pixel level and estimation of the V/Q; the other is the pulmonary gating through which it is possible to identify and quantify the arterio-arterial shunts.(ABSTRACT TRUNCATED AT 250 WORDS)